Circulation of prions within dust on a scrapie affected farm - Gough, Kevin C.; Baker, Claire A.; Simmons, Hugh A.; Hawkins, Steve A.; Maddison, Ben C. (BioMed Central, 2015)
Prion diseases are fatal neurological disorders that affect humans and animals. Scrapie of sheep/goats and Chronic Wasting Disease (CWD) of deer/elk are contagious prion diseases where environmental reservoirs have a direct link to the transmission of disease. Using protein misfolding cyclic amplification we demonstrate that scrapie PrPSc can be detected within circulating dusts that are present on a farm that is naturally contaminated with sheep scrapie. The presence of infectious scrapie within airborne dusts may represent a possible route of infection and illustrates the difficulties that may be associated with the effective decontamination of such scrapie affected premises.